2022
DOI: 10.1111/clr.13972
|View full text |Cite|
|
Sign up to set email alerts
|

Reconstructive surgical therapy of peri‐implantitis: A multicenter randomized controlled clinical trial

Abstract: Objective To evaluate the potential benefit of the use of a bone substitute material in the reconstructive surgical therapy of peri‐implantitis. Methods In this multicenter randomized clinical trial, 138 patients (147 implants) with peri‐implantitis were treated surgically, randomized by coin toss to either a control (access flap surgery) or a test group (reconstructive surgery using bone substitute material). Clinical assessments, including probing pocket depth (PPD), bleeding and suppuration on probing (BOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 31 publications
(55 reference statements)
5
85
4
Order By: Relevance
“…At the 12‐month examination, an overall 26.9% treatment success rate was found. This value is similar or even superior to other trials (Hallström et al, 2017 ; de Tapia et al, 2019 ; Polymeri et al, 2020 ; Renvert et al, 2021 ; Derks et al, 2022 ). However, using the same evaluation criteria, Carcuac et al ( 2016 ) reported a success rate of 45%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…At the 12‐month examination, an overall 26.9% treatment success rate was found. This value is similar or even superior to other trials (Hallström et al, 2017 ; de Tapia et al, 2019 ; Polymeri et al, 2020 ; Renvert et al, 2021 ; Derks et al, 2022 ). However, using the same evaluation criteria, Carcuac et al ( 2016 ) reported a success rate of 45%.…”
Section: Discussionsupporting
confidence: 84%
“…At 6 and 12 months after surgery, an overall soft‐tissue recession of ≅2 mm has been observed, a value which is higher than in other randomized clinical trials (Renvert et al, 2021 ; Derks et al, 2022 ). Differences in the employed surgical approaches may possibly explain this discrepancy, because the present study also included resective surgeries.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In Derks et al (2022), in Table 1, the column representing percentages in the Test Group has shifted in the version published online.…”
Section: Test Control Total N %/Mean (Sd) Min‐max N %/Mean (Sd) M...mentioning
confidence: 99%
“…In the test group, the peri-implant defects were grafted with a demineralized bovine bone mineral (DBBM) containing collagen (Bio-Oss Collagen®, Geistlich, Lucerne, Switzerland). With or without DBBM defect grafting the radiographic defect fill was 1.1 mm in sites with a marginal bone loss of 6.1 mm at baseline [ 4 ]. In another multi-center study with a similar set-up, DBBM (BioOss, Geistlich) covered by a collagen membrane (BioGide, Geistlich) was used in the test group [ 5 ].…”
Section: Introductionmentioning
confidence: 99%